Thyroid function in neonates of women with subclinical hypothyroidism or hypothyroxinemia. (November 2018) - Varner, Michael; Mele, Lisa; Casey, Brian; Peaceman, Alan; Sorokin, Yoram; Reddy, Uma; Wapner, Ronald; Thorp, John; Saade, George; Tita, Alan; Rouse, Dwight; Sibai, Baha; et al.
Abstract Objective To assess whether treatment of pregnant women with subclinical hypothyroidism or hypothyroxinemia alters neonatal TSH results. Study design A planned secondary analysis of data from two multi-center randomized, double-masked, placebo-controlled thyroxine replacement trials in pregnant women with either subclinical hypothyroidism or hypothyroxinemia. Infant heel-stick specimens were obtained before discharge. We compared TSH levels between neonates born to mothers allocated to treatment or placebo within each trial and between neonates in the placebo groups. Multiples of means were generated for day-of-life-specific data. Results Neonatal TSH values were available for 573/677 (84.6%) newborns from the subclinical hypothyroidism trial and 461/526 (87.6%) newborns from the hypothyroxinemia trial. Neonatal TSH values did not differ in either trial by treatment group or between placebo groups (P > 0.05 for all comparisons). Conclusions Neonatal TSH values did not differ with thyroid hormone replacement in pregnancies diagnosed with subclinical hypothyroidism or hypothyroxinemia.